Clinical impact on treatment and prognosis of advanced cardiac imaging with echocardiography in the acute setting of a COVID-19 infection. (14th October 2021) - Gonzalez Del Hoyo, M; Servato, L; Fernandez-Galera, R; Rodenas, E; Garcia, M; Casas, G; Jordan, P; Herrador, L; Bach, M; Valente, F; Gutierrez, L; Baneras, J; et al.
Abstract: Background and objectives: Despite myocardial injury being related to excess mortality in acute COVID-19 infection, its impact on imaging findings remains unclear. This study aimed to characterize transthoracic echocardiographic (TTE) findings in patients admitted with COVID-19 infections and its impact on management and prognosis. Methods: A prospective observational cohort study was performed among 66 COVID-19 patients who were admitted to a tertiary center between March 1 and May 25, 2020 and underwent TTE. High-sensitivity troponin I (hs-cTnI) data, echocardiographic assessment of right and left ventricular (LV) functional parameters, strain, and myocardial work analysis were obtained. Results: 2025 patients were admitted with COVID-19 and in 200 a complete TTE study was performed. Due to poor image quality, only 66 studies were included in the final analysis. The median age was 62 years (IQR, 55–70) and 59.1% of patients were males. The most common comorbidity was hypertension (47%), followed by smoking history (30.3%), atrial fibrillation (9.1%), and chronic obstructive pulmonary disease (7.9%). More than half of the patients (39, 59%) were admitted to the ICU, and half of them (33, 50%) required invasive mechanical ventilation. TTE was mainly indicated because of concerns for systemic conditions (50%) and evaluation of hemodynamic assessment (30%). Thirty-six patients (54.5%) had an abnormal TTE result and 57% had elevated hs-cTnI levels. The most common cardiac abnormality was LV diastolic dysfunction in 33% of the patients, followed by right ventricular dysfunction (12%) and LV dysfunction (6%) (Figure 1). LV GLS was reduced in 48.5% of the cases. Myocardial work performance indices were all reduced in patients with an abnormal TTE (GWI 30%, GCW 30%, GWW 40%, and GWE 40%), although differences were not significant (P>0.2 for all parameters). Patients with an abnormal TTE were older and presented a higher cardiovascular risk profile. There were no significant differences in the levels of D-dimer, NTproBNP, and hs-cTnI between patients with and without diastolic dysfunction, RV, or LV dysfunction (P>0.3 for all parameters). Using Spearman rank correlation, there was an inverse relationship between hs-cTnI and LV strain and myocardial work analysis. TTE results impacted clinical management in 60 patients, mainly de-escalation of medical treatment (Figure 2). Abnormal TTE results did not impact in-hospital outcomes. Conclusions: Severe echocardiographic abnormalities are uncommon in hospitalized patients with COVID-19 infections, presenting mostly with subclinical myocardial changes, such as diastolic dysfunction, reduced LV GLS, and myocardial work indices, both associated with high-sensitivity troponin I elevation. An echocardiographic study should be limited to rule out long-term ICU complications or to evaluate hemodynamic instability. Although TTE was a valuable tool for guiding management, it had no significant impact on prognosis. Funding Acknowledgement: Type of funding sources: None.